MENGURANGI PERILAKU MENGHISAP JARI BAGI ANAK GANGGUAN INTELEKTUAL MELALUI TEKNIK STIMULUS AVERSIF - Siska Oktaviani (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract Siska Oktaviani (2014) : Reducing Suckig Fingers Behavior on The Kids with Intellectual Disturbance through Aversive Stimulus Technique In Class IIIC of SDN(SDLB)35 Painan Utara. Thesis. Undergraduate Program of Faculty of Education of Padang State University   This research was derived from the fact indicating that a kid with intellectual disturbance was frequently sucking his fingers during the learning process and he declined to do the assignment given. While sucking his fingers, the kid had less concern on learning. The ain of this research was to see the effectiveness of aversive stimulus techniqueto reduce sucking fingers behavior of the kid with intellectual disturbance by using empedu tanah(sambiloto). The hypothesis of research was empedu tanah (sambiloto) could reduce sucking fingers behavior of the kid with intellectual disturbance in class IIIC of SDN(SDLB) 35 Painan Utara. This was single subject research with applied A-B-A design. The result of data analysis indicated that in the baseline condition which was conducted for 10 days around 234-120 second, the tendency of the direction improved. Further, in the intervention condition which was conducted for 12 days around 220-55 second, the tendency of direction decreased. In the baseline condition A2 which was conducted for 8 days around 65-40 second, the tendency of the direction also decreased. The result of within and inter-condition data analysis required that the hypothesis whould be accepted if the estimation of direction tendency, stability tendency, data recording and the changing level improved positively, and the percentage of the data overlapped getting smaller. This research concluded that use of aversive stimulus technique cloud reduce sucking fingers behavior of the kid with intellectual disturbance n class IIIC of SDN (SDLB) Painan Utara. Based on the research findings, it was recommended to the teachers and parents to have more concern on the children behaviors and reduce the negative behavior by using aversive stimulus technique. Keyword: Sucking Fingers Behavior